COMPARATIVE ANALYSIS OF SOURCE WAVELENGTH COMBINATION IN MULTI WAVELENGTH PHOTOPLETHYSMOGRAPHY METHOD FOR NON-INVASIVE HBA1C MEASUREMENT - Indahsari, Intan
Diabetes, a chronic condition marked by impaired glucose metabolism, resulted in 1.5 million deaths globally in 2019 and had a prevalence of 10.6% among Indonesian adults in 2021. With no cure available, effective management depends on maintaining healthy lifestyle and regularly monitoring blood glucose levels. Glycated hemoglobin (HbA1c) is a key marker for assessing average blood glucose levels and associated complications. However, traditional HbA1c measurement methods are invasive, which poses challenges in terms of patient comfort, cost, and accessibility, especially in regions with limited clinical resources. This study explores the potential of non-invasive HbA1c measurement using photoplethysmography (PPG) technology, which has been successfully employed for non-invasive blood oxygen level monitoring through light absorption characteristics of hemoglobin. We investigated the use of multiple wavelengths (465, 525, 615, and 880 nm) for measuring HbA1c in 37 research subjects consisting of 13 normal, 10 prediabetic, and 14 diabetic individuals. Our results show that combining blue-red and green-red wavelengths yields the highest correlation, with Pearson’s r values of 0.921 and 0.845, respectively. Clarke's Error analysis indicates that these wavelength combinations achieve accuracy rates of 94.6% and 78.38% in region A, with data primarily falling in regions A and B.